Africa : : Status of women in Africa - Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1937)
Colonial Office file relating to the status of African women in British colonies, including social conditions, education, traditional customs and the adequacy of existing legal protection of their personal safety and freedoms against coercion and abuse